Dealing with Zakat Money, And Its Effect on the Interruption of One Hijri Year: An Applied Jurisprudence Study - Al-Tawalbeh , Mohammad (Dirasat: Shari’a and Law Sciences, 2021)
The research deals with the effect of disposing of zakat money by selling or exchanging, and what related to the termination of contracts or their reimbursement by choice or defect in discontinuance about zakat, and concerns with collecting and studying a comparative juristic study, which contributes to highlighting the reality and the inclusion of zakat jurisprudence, and the attention from Sharia to those whom are charged with it. The research presents various issues regarding the interruption of the Hawl, which is the length of time that an individual must possess the wealth that they will pay Zakat on. The study adopted the inductive method to state the issues related to the causes of interruption of Hawl, and its judgments. The study also used the deductive method by considering the statements of Jurists, their evidence, discussing them, weighting between them, and applying their statements to similar issues. Moreover, the comparative method used to balance the statements of jurisprudence. The study concluded the difference of jurists in matters of interruption of Hawl in Zakat due to what affects the property, or disturbs its growth. And it is likely that the Hawl will be interrupted by replacing money with other properties, and by disposing of money to remove the property, even if with the intention is escaping Zakat. Moreover, Hawl can be interrupted by minimizing the Nisab to develop money as trade.